1999
DOI: 10.1063/1.478563
|View full text |Cite
|
Sign up to set email alerts
|

Computer simulation studies of anisotropic systems. XXX. The phase behavior and structure of a Gay–Berne mesogen

Abstract: The Gay–Berne potential is proving to be a valuable model with which to investigate the behavior of liquid crystals using computer simulation techniques. The potential contains four independent parameters which control the anisotropy in the attractive and repulsive interactions. The choice of these parameters is not straightforward and it would seem that those employed in some simulations are not strictly appropriate for mesogenic rodlike molecules. Here we report a detailed computer simulation study of Gay–Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
176
3
7

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 236 publications
(201 citation statements)
references
References 38 publications
15
176
3
7
Order By: Relevance
“…Different versions of the potential are identified by the GB(κ, κ , µ, ν) notation of Bates and Luckhurst [12]. As in our previous work [13,14] we have simulated GB(3,5,2,1), the original suggestion of Gay and Berne [9], for which the phase diagram has been well studied [15], and GB(3,5,1,3),…”
Section: Simulation Detailsmentioning
confidence: 99%
“…Different versions of the potential are identified by the GB(κ, κ , µ, ν) notation of Bates and Luckhurst [12]. As in our previous work [13,14] we have simulated GB(3,5,2,1), the original suggestion of Gay and Berne [9], for which the phase diagram has been well studied [15], and GB(3,5,1,3),…”
Section: Simulation Detailsmentioning
confidence: 99%
“…6,9,12 Simulations using different combinations of parameters have shown that the GB model exhibits an additional phase identified as smectic A ͑SmA͒. [15][16][17][18] All these simulation studies suggest that the occurrence of the SmB is not very sensitive to the particular parameterization, whereas the formation of the SmA phase requires the molecular elongation be large enough.…”
Section: Introductionmentioning
confidence: 99%
“…These were determined by maximising S k with respect to the layer spacing by a method similar to that used in [24]. To do this, firstly a suitable part of a run, where stable smectic layers had formed, was selected.…”
Section: Nmentioning
confidence: 99%